The Coated-Wire Ion Selective Electrode (CWISE) of Chromate Using PVC-Membrane Based on Chitosan as A Carrier - Dedeh Kurniasih; Atikah Atikah; Hermin Sulistyarti (The Journal of Pure and Applied Chemistry Research, 2012)
A coated-wire ion selective electrode (CWISE) based on chitosan as a carrier for detection of chromate, was developed. CWISE has easy measurement for field analysis, good selectivity and sensitivity. The CWISE’s membrane consist of mixture an active material of chitosan, aliquat 336-chromate, polyvinylchloride (PVC) and dioctylphtalate (DOP) as plasticizer = 4:0.5:35:60.5 (% w/w) dissolved in tetrahydrofuran (THF) solvent (1:3 w/v). The electrode exhibited a good Nernstian slope of 29.77±0.03 mV/decade and a linear concentration range from 10-6 to 10-1 M for chromate. The limit of detection was 1.862 x 10-6 M. It had response time of 20 – 40 sec, and could be used for 49 days. This chromate selective-electrode was found more selective towards the chromate ion than other anions, useable in pH range of 5.0 – 9.0 and temperature of 20 – 50 oC. It was applied as an electrode for direct determination of chromate in water samples and their result compared to standard spectrophotometric method.